Exercising recommendations for paroxysmal AF in young and middle-aged athletes (PAFIYAMA) syndrome - Perez-Quilis, Carme; Lippi, Giuseppe; Cervellin, Gianfranco; Löllgen, Herbert; Sanchis-Gomar, Fabian (Annals of Translational Medicine; Vol 5, No 1 (January 13, 2017): Annals of Translational Medicine (Focus on “MET as Actionable Target in Cancer Therapy”), 2017)
We have recently described a new syndrome: strenuous endurance exercise-related atrial fibrillation (AF) under the acronym of ‘paroxysmal AF in young and middle-aged athletes’ (‘PAFIYAMA’). Provided that other risk factors for AF and underlying conditions have been excluded (1), the diagnostic criteria for this syndrome entail a number of conditions, classified as major and minor. An enhanced risk of AF has been clearly documented in endurance athletes (top-class, elite and recreational) (2-5), and such risk typically ranges between 1.2- to 15-fold compared to the general, sedentary population (the better cardiovascular fitness, the higher incidence of AF) (6-11). Anecdotally, the last author of this manuscript (F Sanchis-Gomar), a physician himself, was a competitive endurance cyclist for 10 years and a paradigm of PAFIYAMA syndrome. Briefly, he has suffered from left atrial enlargement and a first episode of paroxysmal AF early in life, at the age of 26 years. After 5 years of recurrent episodes, pulmonary vein isolation by trans-venous cryoablation seemed to be the only successful treatment. Although he has suffered no more AF episodes since then, high-intensity exercise would be no longer advisable.